Assessing Social Sustainability in Mosque as Religious Building, Case Study: Al-Lathiif Mosque, Bandung-West Java, Indonesia - Indrarani, Indri Astrina Fitria; Sari, Shaufa Salsabila; Lukman, Aldyfra Luhulima; Sahid, Sahid (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2025)
A mosque is a place of worship for Muslims that emphasizes the concept of Rahmatan Lil Alamin, meaning to bring blessings to all people. Based on this statement, a mosque serves as a safe and comfortable space for performing ritual prayers and as a venue for accommodating social activities for its congregants. The function of mosques evolves, especially during the month of Ramadan. It becomes more active and serves various purposes beyond prayers, including religious, political, economic, educational, commercial, social, and cultural activities. All of these activities aim to foster social interaction among Muslim communities. This research aims to uncover the behavior and movements of worshippers during both Salat ritual and non-Salat activities within mosque spaces. The study focuses on Al-Lathiif Mosque in Bandung, known for its vibrant young community, which engages in diverse and active activities. The steps taken to achieve the research objectives are as follows: (1) Identifying the indicators to reveal social sustainability through literature studies; (2) Mapping the behavior of congregants and the utilization of mosque spaces during Salat activities; (3) Mapping the behavior of congregants and the utilization of mosque spaces during non-Salat activities; (4) Distributing questionnaires related to social sustainability indicators regarding space utilization in the mosque; (4) Concluding the application of social sustainability concepts in mosque spaces. The analysis results reveal that social sustainability is optimally achieved in the flexibility of spaces in a mosque.